FRONTIERS TRANSGRESSIONS AND THE EVOLUTION OF ILLEGAL PRACTICES IN THE CENTRAL AFRICAN STATES BEFORE THE ADVENT OF BOKO HARAM INSURGENT: A HISTORICAL STUDY DURING RECENT TIMES - MONTEH, René NGEK (PEOPLE: International Journal of Social Sciences, 2019)
Frontiers in Africa are areas fostering mobility and cross-border trade despite state limits. These frontiers have come to be a natural feature in human lives. They designate not only the limits and jurisdictions of states, but also an essential reference of national identity since they regulate movements of people, goods and services. In an era of global inequality of mobility rights, freedoms of mobility for some nationals have coexisted with the systematic exclusion of others. Since independence, the Central African States are developing an interest in cross-frontier cooperation. Frontiers are nodes of contacts, of conflicts and of cooperation all depending on the policies put in place by member States. This explains why frontiers in the study area are subjected to openness or closure. However, despite the role played by member States, Sub regional and regional organizations such as CEMAC, ECCAS and AU amongst others, the phenomenon of frontiers transgression still remain a bitter truth experience. The underway cross-frontiers perspective seems to militate for the openness option. This trend has been growing for the past decades at times because of the slow process of institutionalization and incorporation of cross-frontier cooperation in Central African development policies at national level. Drawn from our various sources especially primary data, this paper attempts to illustrate the dramatic characteristics and evolution in frontier transgression within Central African States. In this sphere, the countries evoked here are Cameroon, CAR, Chad, Nigeria and Sudan. Issues such as dual nationality, cross-border prostitution, arms trafficking, contraband, large-scale trafficking and theft, and attempted solutions are discussed in this paper.